Bioassay-guided fractionation of Emilia sonchifolia extract on the induction of ovarian maturation in Fenneropenaeus merguiensis - Lamai Maikaeo,; Wilawan Mahabusarakam,; Wilaiwan Chotigeat, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study was carried out to identify the active compounds of Emilia sonchifolia on induction of ovarian maturation in Fenneropenaeus merguiensis. The crude extracts from dichloromethane and acetone were investigated in vitro. The crude extract from acetone induced up-regulation of shrimp ovarian peritrophin (SOP) and translationally controlled tumor protein (TCTP) genes, which were highly expressed during early phase of ovarian development higher than dichloromethane extract. Furthermore, fraction 14 (F14) from acetone extract up-regulated both of the SOP and the TCTP genes to the greatest extent. Leading to in vivo study, the effect of ribosomal protein L10a (RPL10a), which acts as shrimp ovarian stimulator plus with F14 on shrimp ovarian maturation was investigated by injection. The best result was observed in the group that received RPL10a plus with F14 at 0.8 μg/g body weight of shrimp. The RPL10a plus F14 enhanced the shrimp ovaries from undeveloped stage to 57% of early developing stage within 15 days. Meanwhile, the control group remained 100% of the undeveloped stage. Hence, F14 seems to play a positive role in the induction of shrimp ovarian maturation. The component of F14 was identified using mass spectroscopy and presented as 1,2-benzenedicarboxylic acid; 2,4-di-tert-butyl phenol; 2,4,5-trimethoybenzylidene;palmitic acid; 1-heneicosyl formate; 1-heptadecanol; ethyl-4-ethoxybenzoate and stearic acid.